Respuesta :

Answer:

(1, 6 )

Step-by-step explanation:

Given the 2 equations

3x - 2y = - 9 → (1)

4x + 3y = 22 → (2)

Multiplying (1) by 3 and (2) by 2 and adding the result will eliminate the x- term

9x - 6y = - 27 → (3)

8x + 6y = 44 → (4)

Add (3) and (4) term by term

17x = 17 ( divide both sides by 17 )

x = 1

Substitute x = 1 into either (1) or (2) and solve for y

Substituting in (2)

4(1) + 3y = 22

4 + 3y = 22 ( subtract 4 from both sides )

3y = 18 ( divide both sides by 3 )

y = 6

Solution is (1, 6 )